Propriedades mecânicas de tração e impacto dos aços inoxidáveis CA15 e CA6NM - Paula, Luiz Cláudio Araújo de (Universidade Federal de São Carlos, 2007)
The subject of this work was to study the mechanical properties, based in tensile and impact tests, of two stainless martensitic steels cast under designations of ASTM Standards, namely the CA15 steel, a steel with 12% of Cr, and the CA6NM steel, a steel with 12% Cr and 4% Ni. For both steel grades bar tests were machined out from Keel Block coupons test cast in sand molds bonded with no-bake resin, according to the ASTM designations. Before machining the Keel Blocks were heat treated according to the ASTM standards as following: solubilization, quenching and tempering. The effectiveness of the heat treatments and the results of the mechanical tests were evaluated by means of microstructural characterization using optical and scanning electron microscopies. The CA15 steel showed the presence of delta ferrite in the martensitic matrix, and a weak tendency to carbide precipitation. On the other hand, the CA6NM steel showed predominantly a martensitic structure and strong carbide precipitation. The effect of two quenching conditions, namely water and air, were investigated on the mechanical properties of CA15 and CA6NM steels and showed to be high significance. For both steels two distinct levels of tensile strength at room temperature were obtained, one inferior to 700MPa, and other superior around the 900MPa. In the CA15 grades were obtained higher values of area reduction and lower elongation values, when compared to the CA6NM grade. The tensile tests at higher temperature (500°C), led to a reduction of approximately 30% in the values of tensile strength for the CA15 steel. However, in the CA6NM steel, the reduction of the tensile strength was lower( less than 20%) due to presence of massive carbide precipitation. After impact tests at several temperatures for determination of the ductile-fragile transition temperature, according to the 20,6J criterion, the CA15 steel revealed a transition temperature beyond 10°C, while the CA6NM steel revealed values between -100 and -150°C.
Mechanical properties of cast CA15 and CA6NM stainless steels
Keywords: Aço inoxidável fundido; Propriedades mecânicas; CA15; CA6NM; Austenita retida; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA